Gold Nanoclusters as High Resolution NIR-II Theranostic Agents - Sharma, Nancy; Mohammad, Walaa; Le Guével, Xavier; Shanavas, Asifkhan (Chemical & biomedical imaging, 2024)
In the realm of nanomaterials, atomically precise quasi-molecular gold nanoclusters (AuNCs) play a prime role due to their unique, stable, and highly tunable optical properties. They are extensively structure-engineered for modulation of surface electronic states toward long wavelength photoluminescence, particularly in the NIR-II (1000 to 1700 nm) window. Contrast agents with NIR-II emission can potentially transform optical imaging in terms of higher spatial resolution, deeper tissue penetration, and reduced tissue autofluorescence. These advantages allow real-time imaging in living organisms for observing disease progression and treatment response. In this short review, we discuss origin of NIR-II emission in rationally designed AuNCs and their application toward high resolution imaging of vasculatures and hard and soft tissue structures for identification of pathological conditions such as stroke and injury. Further, recent employment of these AuNCs in the rapidly growing field of tumor theranostics is also summarized. Final remarks are provided on the scope for improvement in their optical properties and persisting challenges for clinical translation.